An optimal voltage stability enhancement in the power systems by locating optimal place with more contingency risk - Rajalakshmi P; Rathinakumar M (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
The electrical components of a power system network take advantage to supply, transmission and service electrical power. Abnormal flow of voltage through the transmission lines might lead to big causes. Thyristor controlled series compensator (TCSC) devices are most frequently used device in the power to maintain the voltage stability. However, this device is costlier and cannot be fixed on every transmission line which would lead to more processing cost. Thus, the maintaining voltage stability of transmission lines with reduced production cost attracts a various researcher to find the novel approaches. In the existing system, to improve the stability of power system and minimize the losses by include the reactive power through TCSC device at applicable location by the algorithm of particle swarm optimization is available with the help of line stability index value. The PSO is constrained to poor exploitation problem which might generate inaccurate results. In the proposed research work, Biogeography Based Krill Herd (BBKH) method is used for optimal identification of TCSC's, STATCOM and UPFC size and location. Voltage collapse proximity indicator (VCPI) value is used in this work for the finding of the voltage instability measurement by finding the critical lines among the entire transmission lines. The proposed research effort is implemented in IEEE 39 test bus system using MATLAB software and verified, it furnishes improved outcome than other investigation methodologies.